తెలంగాణ చరిత్ర - Venkata Ramarao, G. (Andhra Saraswata Parishath, 2015)
It's all about Telangana history
Telangana Charitra
Keywords: Telugu; తెలంగాణ చరిత్ర; Telangana Charitra; Literature; Telugu; Telugu